RESPONS PERTUMBUHAN BIBIT KAKAO TERHADAP VERMIKOMPOS DAN PUPUK P - Onny Suriyono Silaen Onny Suriyono Silaen Onny Suriyono Silaen; Ferry Ezra Sitepu; Balonggu Siagian (Jurnal Agroekoteknologi, 2013)
Response of Cacao (Theobroma cacao L.) Seedlings Growth on Application of Vermicompost andP Fertilizer. The research was conducted to determine response of cacao seedlings growth onapplication of vermicompost and P fertilizer. The research carried out at Faculty of AgricultureUSU’s Experiment Land with a height of 25 metre above sea level on August until November 2012by using Randomized Block Design of two factors which is the first factors were vermicompost(0%, 25%, 50%, 75%) and the second factor were P fertilizer (0, 2, 4, 6 g/plant). The parametersobserved were seedling height, leaf number, stem diameter, total of leaf area, seedling wet weight,seedling dry weight, root wet weight, root dry weight and shoot root ratio. The results showed thatvermicompost has significant effects on seedling height, leaf number and seedling dry weight. Theapplication of P fertilizer and interaction of them had no significant effects on all parametersobserved.Key words : vermicompost, phosphat, cacao